Hemipenes eversion behavior: A new form of communication in two liolaemus lizards (iguania: Liolaemidae) - Ruiz Monachesi, Mario Ricardo (2018)
Males of several animals have intromittent organs and may use these in a communicative context during sexual or intrasexual interactions. In some lizards, hemipenes eversion behavior have been observed, and the aim of this study is to find out whether this behavior is functionally significant under a communicative approach. Here, we investigated the eversion of hemipenes in the Light Blue Lizard (Liolaemus coeruleus Cei and Ortiz-Zapata, 1983) and in the Valley Lizard (Liolaemus quilmes Etheridge, 1993) by filming the response of male focal lizards in different experimental settings: (i) an agonistic context, i.e., with a conspecific male, (ii) a sexual context, i.e., with a conspecific female, and (iii) a control treatment, i.e., without a treatment lizard. In both species, focal lizards showed this behavior only in an agonistic context, with interspecific differences as follows. Liolaemus coeruleus has longer times until eversion and dragging of hemipenes; however, it has shorter time of eversion and exposition of the hemipenes. Liolaemus quilmes has the opposite pattern compared with L. coeruleus. These indicate that eversion of the hemipenes can act as a visual display and as a signal of aggressive behavior towards conspecific rival males. The present study offers a new behavioral perspective on the use of masculine genitalia in lizards.